AN ASSESSMENT OF LAND USE AND LAND COVER CHANGE IN MANGA GRASSLAND OF YOBE STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Human activities and natural events continually reshape land use patterns, underscoring the critical need for accurate land use information in various applications such as natural resource management and environmental monitoring. Land use change has become pivotal in current strategies for these purposes globally. The rapid advancements in land use mapping have spurred increased studies worldwide, aiming to assess and monitor the extent and health of forests, grasslands, and agricultural lands. Remotely sensed data, including aerial photographs and satellite imagery, are indispensable for extracting precise land use change information. This study focusing on Manga grassland (Machina, Yusufari, and Yunusari LGAs), satellite images from Landsat TM (1988), Landsat ETM (1998), Landsat ETM+ (2008), and Landsat 8 (2018) for image classification. The study employed supervised classification methods to analyse land use changes, revealing significant alterations in vegetation cover over the study period. In conclusion, it was observed that observed that vegetation cover increases from north toward the south follow the trend of rain fall, over-cutting, over grazing, and other climatic factors, which determines species distribution.  Vegetation degradation is detected more in north boundary Niger republic. This may be due to southern flow of the Sahara Desert into the northern part of Nigeria around the study area. Data analysis shows that land use land cover had been changing through the study zones and this change had negative impact on natural resource development. Finally, it was recommended that the development of suitable and adequate mean of awareness for local community on the importance of species...
Keywords: Land use Change; Remotely Sensed Data; Aerial Photographs; Satellite Imageries; Landsat 8,; Landsat TM; Landsat ETM; Landsat ETM Supervised Classification